DIVERSIDAD EN LOS MODOS DE GESTIONAR LA CONFLICTIVIDAD: profundizando el derecho al acceso a la justicia - Ramírez, Silvina (Universidade de Brasília, 2017)
The right to access to justice comprises a set of topics that must be clarified in order to understand the best way of guaranteeing it. Among these, the administration of indigenous justice is central, since it contributes with its recognition to the deepening of this right. On the other hand, the coordination and articulation of all the existing mechanisms of justice administration become necessary to create a state of situation in which all citizens obtain answers to their conflicts.